The child in the family and the community - Gonzalez-Mena, Janet (Upper Saddle River, N.J. : Merrill, 1998)
This book is about: The child: socialization in a developmental context; The family: Socialization for High self-esteem in healthy families; The Community: Socialization in the community context.
Keywords: Family; Child rearing; Socialization; Socialization; Child rearing; Family